Potensi Bubur Ase Sebagai Daya Tarik Wisata Kuliner Jakarta - Lila Muliani (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2019)
Food and tourism can not be separated. Travellers will always need food to fill his stomach.  However, trend of culinary tourism which begun to be popular in the beginning of the year 2000 has come to the definition that food is not only something to satisfy someones’ hunger. Traditional food of one destination could become an attraction to motivate tourists to come.Jakarta as the capital city that never stop welcoming tourists – domestic and abroad - to come, has many potential culinary attractions. Unfortunately,until today, traditinal food of Betawi - Jakarta people – that is known by people are very limited in number.  The delightfull of Betawi cuisine is not yet being tourist attractions.This study was conducted to analyze Bubur Ase, one of Betawi cuisine, to become a culinary attractions for tourist to come. This special dish is very unique since it is a mixture of porridge, beef stew in sweet soy sauce, and vegetable pickles. The taste is different from another porridge that is already famous. This qualitative research uses primary data from observations, FGD, and in depth interview with Betawi culinary experts. SWOT analysis is used to get a whole picture of internal and external factors that is affected Bubur Ase.The resulf of the study shows that Bubur Ase is potential to become an attractiom for culinaru tourism in Jakarta. The uniqueness and harmonization of taste, historical stories, cultural values and philosophies in a bowl of Bubur Ase are the strenghts that can be developed and promoted. Some weaknesses and threats could be overcome if this dish is already popular. Food and tourism can not be separated. Travellers will always need food to fill his stomach.  However, trend of culinary tourism which begun to be popular in the beginning of the year 2000 has come to the definition that food is not only something to satisfy someones’ hunger. Traditional food of one destination could become an attraction to motivate tourists to come.Jakarta as the capital city that never stop welcoming tourists – domestic and abroad - to come, has many potential culinary attractions. Unfortunately,until today, traditinal food of Betawi - Jakarta people – that is known by people are very limited in number.  The delightfull of Betawi cuisine is not yet being tourist attractions.This study was conducted to analyze Bubur Ase, one of Betawi cuisine, to become a culinary attractions for tourist to come. This special dish is very unique since it is a mixture of porridge, beef stew in sweet soy sauce, and vegetable pickles. The taste is different from another porridge that is already famous. This qualitative research uses primary data from observations, FGD, and in depth interview with Betawi culinary experts. SWOT analysis is used to get a whole picture of internal and external factors that is affected Bubur Ase.The resulf of the study shows that Bubur Ase is potential to become an attractiom for culinaru tourism in Jakarta. The uniqueness and harmonization of taste, historical stories, cultural values and philosophies in a bowl of Bubur Ase are the strenghts that can be developed and promoted. Some weaknesses and threats could be overcome if this dish is already popular.